Steps for the Future of Bulan Bintang Party - Hasrat Efendi Samosir (Budapest International Research and Critics University, 2021)
The aims of the study discuss about the Steps for the Future of Bulan Bintang Party. This study used qualitative research. The result of this study shows that One of the national work programs that were not optimal during the 2005-2010 term of service of the PBB DPP was the consolidation of the organization and the burden of infrastructure formation in most sub-districts and sub-districts/villages. That the political machinery of party management is one of the strategies to achieve success in the face of general elections. Thus, it is necessary to consolidate the organization and complete the formation of party infrastructure down to the lowest level (Rukun Tetangga/RT). Simultaneous and continuous cadre of members in each party is one of the determinants of progress for the party. However, the reality shows that party regeneration is still relatively limited. Therefore, it is necessary to carry out more massive, intelligent, and measurable cadre cadres in order to meet the qualification needs of party management at all levels, preceded by cadre workshops.